Study of Concrete Strength Parameters Using Metakaolin as a Partial Replacement of Cement and M Sand as Fine Aggregate - ., Sangeetha; ., Rishisha (International Journal of Engineering and Technology, 2018)
Metakaolin is a pozzolanic material that is produced by high quality kaolin heated to a temperature between 600â°C-800â°C. It is the most efficient and widely used mineral admixtures in concrete these days. Because of its pozzolanic properties, it can also be used to replace cement to make High Performance Concrete (HPC) mixes. Metakaolin helps concrete to obtain both higher strength and economy. The aim of the research is to find out the compressive strength, split tensile strength ad flexural strength of concrete made with partial replacement of cement with Â metakaolin and Msand as fine aggregate. Cement is replaced with metakaolin in proportions of 5%, 10%, 15%, 20% ,25% & 30% and its strengths compared with the controlled specimens. From the experimental study, it is concluded that concrete containing metakaolin has higher compressive strengths, tensile strengths and flexural strength as compared to controlled specimen and it give better results when replaced upto 25%.Â Â